If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -1) = 3 Reorder the terms: 2(-1 + x) = 3 (-1 * 2 + x * 2) = 3 (-2 + 2x) = 3 Solving -2 + 2x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 2x = 3 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = 3 + 2 2x = 3 + 2 Combine like terms: 3 + 2 = 5 2x = 5 Divide each side by '2'. x = 2.5 Simplifying x = 2.5
| 5(3x-2)=5 | | -6(q-6)= | | -2(4v-w)+4(3w+4v)= | | -3wv-w-wv-3w= | | -4(-2w+y)-5(-3y-6w)= | | 288-7x=38x+23 | | 3.12+8.4x+9.33=6.2x-4.2 | | 4(4u-1)+u= | | 5x+x-5=8 | | -2(y-3)= | | -(4y-u)+6(u+3y)= | | 137-5x=5x+17 | | 2x+16=93-6x | | 10+4x=31+x | | 6x+22=16x-78 | | 57x(-78)= | | 24-(-21)+3-(-3)= | | -54-15= | | 27-(-37)= | | 50-77= | | 3(5+2)=36 | | -7+(-15)= | | 7d+1d-4d-7=5d | | 6(3x-4)=19x | | 6x+7=2x+20 | | 2x+x-59=-70 | | 93-28x-59=10 | | 116-4x=41x+16 | | 10-9x=112-30x | | 5x-6y=90 | | 56-3x=7x+16 | | 7Y+9(18-Y)=150 |